Trophic State of The Lubuk Siam Lake, Based on Nygaard Index - Fella Ferdiana; Madju Siagian; Tengku Dahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTNygaard Index can be used to determine the trophic state of waters. Calculation of this index is based on the number of phytoplankton species in these following groups, namely  Desmidiaceae, Myxophyceae, Chlorococcales, Centric diatom, Pennate diatom and Euglenophyceae. To understand the trophic state of the Lubuk Siam lake, a research has been conducted in February - March 2017. There were three sampling stations, namely station 1 (inlet area), station 2 (the middle of the lake) and station 3 (outlet area). In each station there were three sampling points, in the surface, 2 secchi depth, and 3 secchi depth. Sampling were conducted 3 times, once/week. Water quality parameters measured were phytoplankton (species and abundance), transparency, temperature, pH, nitrate, phosphate, Dissolved oxygen and free carbon dioxide. Results shown that there are 53 species of phytoplankton present, namely Desmidiaceae class (11 species), Myxophyceae class (6 species), Chlorococcales ordo (23 species), Centric   diatom ordo (6 species), Pennate diatom (5 species) and Euglenophyceae division (2 species). The water quality parameters were as follows: transparency 63-89 cm, temperature 28.5-30.53 0C, pH 6.83-7.27, nitrate 0.7-0.17 mg/L, phosphate 0.12-0.16 mg/L, Dissolve oxygen 4.10-7.84 mg/L, free carbon dioxide 5.29-15.98 mg/L. Nygaard Index value of the Lubuk Siam Lake was 2.1 – 2.83, and it can be  categorized as mesotrophic to eutrophic. Keywords: Lubuk Siam lake, Nygaard Index, phytoplankton, trophic state